LAParoscopic simulator for pediatric ureteral reimplantation (LAP-SPUR) following the Lich-Gregoir technique. Issue 2 (April 2018) - Millán, Carolina; Rey, Mercedes; Lopez, Manuel
Summary: Objective: Acquiring surgical skills requires regular practice. Medical evidence supports that these skills can be learned outside the operating room (OR). The aim of the current study was to describe the first laparoscopic simulator for ureteral reimplantation (LAP-SPUR) following Lich- Gregoir technique. Materials and methods: LAP-SPUR was manufactured using reusable and disposable materials. The technique can be summarized in the following five steps: (1) a transperitoneal approach; (2) extra-vesical ureteral dissection; (3) detrusor division until exposing the mucosa; (4) reimplanting ureter into the new tunnel; and (5) reapproximation and suturing of the detrusor. LAP-SPUR was evaluated through a survey answered by urologists and surgeons. A 5-point Likert scale was employed for most items and the medians test was chosen to compare the response among physicians according to the number of laparoscopic surgical procedures performed per week (≤2 versus >2) and the experience in ureteral reimplantation of the respondent as a dichotomous variable (0 versus ≥1 repairs). Results: Thirty-four surveys were answered. The simulator was reported to: have a very high level of realism by the experts; be a reproducible procedure with similar anatomical structures and working space to pediatric patients by the non-experts; be extremely useful, easy and ergonomic for laparoscopic training outside the OR; be lightweight and portable for straightforward transportation; be inexpensive; and be reusable and have low maintenance requirements. It was found to provide a secure environment for trainees, to enhance cognitive knowledge acquisitions, and to increase technical performance. Only tissue handling was non-significant when groups were compared. Conclusion: Augmenting surgical dexterity using LAP-SPUR offered great promise because maneuvers could be rehearsed over and over until they were mastered. Of the urologists and surgeons who were evaluated, 100% reported lack of training at their institutions; therefore, all of them would definitely benefit by practicing with LAP-SPUR to enhance technical skill acquirement. Further development and validation are still needed to assess its true benefits.